2017
DOI: 10.1108/aia-06-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Fathers experiences of sleeping problems in children with autism

Abstract: Research limitations:The interview sample cannot be said to be representative of all fathers of children with autism since the backgrounds of those taking part were relatively homogeneous in respect of ethnicity, marital status and level of education.Practical implications: Improvements in effective, family-centred provision are urgently needed which employ a co-parenting, gender-differentiated methodology. Social implications:Given the severity and frequency of difficulties, sleeping problems in children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The lack of inclusion experienced by several fathers in the diagnostic process can be contextualised within findings from the wider survey associated with this study (Potter, forthcoming) where six in ten fathers felt that they had not been adequately supported “as the child's father” in the period following diagnosis. Such perspectives are suggestive of a deficit model approach implicit in the attitudes of practitioners encountered and it is consistent with findings from other studies in the field of disability where provision has been found to be generally targeted at mothers (see Flippin and Crais, ; SCIE, ; Towers, ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The lack of inclusion experienced by several fathers in the diagnostic process can be contextualised within findings from the wider survey associated with this study (Potter, forthcoming) where six in ten fathers felt that they had not been adequately supported “as the child's father” in the period following diagnosis. Such perspectives are suggestive of a deficit model approach implicit in the attitudes of practitioners encountered and it is consistent with findings from other studies in the field of disability where provision has been found to be generally targeted at mothers (see Flippin and Crais, ; SCIE, ; Towers, ).…”
Section: Discussionsupporting
confidence: 86%
“…Findings from the wider survey, from which the current data set is drawn found that over half of all fathers (52%, 161/306) felt that having a child with autism had negatively affected their couple relationship (Potter, forthcoming) resonating with the results of a meta‐analysis which found relationship satisfaction amongst couples having children with autism to be lower than amongst those having children without disabilities (Sim, Cordier, Vaz, & Falkmer, ). The year following diagnosis has been reported as imposing particular stresses on couples (McGrew & Keyes, ) and here, insights into the kinds of pressures which diagnosis placed on relationships are provided from the paternal perspective.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations